COST-EFFECTIVE AND EFFICIENT BLOCKCHAIN FRAMEWORK FOR VERIFYING CERTIFICATE IN YEMENI UNIVERSITIES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Recognizing the necessity to preserve the integrity and good name of degrees awarded by Yemeni universities. It should provide an efficient way of verifying certificates. The effectiveness of the conventional method of confirming the validity of certificates in reducing fraud has not been very strong. Therefore, it is necessary to stop this kind of fraud by using blockchain technology, which has several benefits, such as encryption, sharing of data, and the capacity to store information as permanent data that cannot be altered. Low latency and low cost will be available for the issuance, sharing, and verification of these certifications in universities if the suggested system is implemented. The paper presents the proposed framework, which uses smart contracts in the Ethereum blockchain and a distributed peer-to-peer network (filebase) for certification verification by a certificate’s hash immediately without waiting for the facility’s response. It also contains an estimate of the average cost of publishing a certificate. It also frees students from having to constantly carry paper copies of their documents by enabling them to access them via a certificate's hash. Furthermore, there is no extra cost for the verification process, and it does not require an Ethereum network account.